Hubungan Perilaku Sedentari Terhadap Status Gizi Remaja Pengguna Game Online Saat Pandemi Covid-19 - Elizabeth Suryani Parhusip; Linda Riski Sefrina (Jurnal Ilmiah Wahana Pendidikan, 2022)
Distance Learning (PJJ) during the pandemic increased sedentary behavior caused by lifestyle problems in today's youth, namely a sedentary lifestyle that is influenced by the environment, with one of the activities being playing games. This study aims to examine the relationship between sedentary behavior and nutritional status in adolescent online game users during the Covid-19 pandemic at SMKS Jayabeka 01 Karawang. This research method uses a cross-sectional research design. The research sample was the students of SMKS Jayabeka 01 Karawang totaling 155 respondents. The sample was taken using a simple random sampling technique. Collecting data using observation, interviews and questionnaires with the test used is Gamma. The results of the analysis of this study are that there is no significant relationship between sedentary behavior and nutritional status with a p-value of 0.623 (p>0.05) in adolescent users of online games at SMKS Jayabeka 01 Karawang during the Covid-19 pandemic.